2018
DOI: 10.1002/advs.201800036
|View full text |Cite
|
Sign up to set email alerts
|

B, N Codoped and Defect‐Rich Nanocarbon Material as a Metal‐Free Bifunctional Electrocatalyst for Oxygen Reduction and Evolution Reactions

Abstract: The development of highly active, inexpensive, and stable bifunctional oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts to replace noble metal Pt and RuO2 catalysts remains a considerable challenge for highly demanded reversible fuel cells and metal–air batteries. Here, a simple approach for the facile construction of a defective nanocarbon material is reported with B and N dopants (B,N‐carbon) as a superior bifunctional metal‐free catalyst for both ORR and OER. The catalyst is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(98 citation statements)
references
References 61 publications
2
95
1
Order By: Relevance
“…It is found that the contents of pyridinic N and graphitic N are clearly higher than that of pyrrolic N, suggesting the excellent electrocatalytic activity of BN‐CA‐900 for ORR may be expected according to the previous reports . The B 1s high‐resolution spectra of the BN‐CA‐900 (Figure d) show four peaks at 190.2, 191.1, 192.3, and 190.7 eV, which could be ascribed to the BC 3 , BC 2 O, BCO 2 , and B−N configurations, respectively, indicating the multi‐model existence of B in BN‐CA‐900. The XPS analysis proves that we have successfully synthesized B, N co‐doped carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the contents of pyridinic N and graphitic N are clearly higher than that of pyrrolic N, suggesting the excellent electrocatalytic activity of BN‐CA‐900 for ORR may be expected according to the previous reports . The B 1s high‐resolution spectra of the BN‐CA‐900 (Figure d) show four peaks at 190.2, 191.1, 192.3, and 190.7 eV, which could be ascribed to the BC 3 , BC 2 O, BCO 2 , and B−N configurations, respectively, indicating the multi‐model existence of B in BN‐CA‐900. The XPS analysis proves that we have successfully synthesized B, N co‐doped carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, carbon defects are also created by the release of some gases from the decomposition of the precursor during the graphitization process. Numerous studies have shown that carbon defects are favorable to provide more active sites and the transfer of electrons, which are beneficial to accelerate the ORR process.…”
Section: Resultsmentioning
confidence: 99%
“…There are two kinds of lattices of 0.190 nm and 0.208 nm in the HRTEM images of Fe x C y N z /N‐CNT‐30, which corresponds to the (110) plane of Fe and the (021) plane of Fe 2.5 C or the (111) plane of Fe 3 N, respectively . In addition, Figure f reveals the well‐graphitized carbon layers with some broken fringes in the shells and a twisted morphology . By combining with HRTEM and the Raman spectra results, it is can be reasonably deduced that Fe x C y N z /N‐CNT‐30 possesses abundant carbon defects, which is believed to play a positive effect on ORR activity.…”
Section: Resultsmentioning
confidence: 99%
“…In general, heteroatom doping often induces crystalline disorder and representative defects, such as vacancies, lattice reconstruction, and dangling groups, which could also significantly enhance the catalytic activities . Extensive research efforts have been devoted to investigating the nanostructured carbon with both heteroatom doping and abundant structural defects for oxygen catalysis in ZABs . Studt et al.…”
Section: Carbon‐based Bifunctional Oxygen Catalystsmentioning
confidence: 99%